Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/app.40658
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of ethylene and propylene polymerization over titanium–magnesium catalysts of different composition

Abstract: New data on the molecular weight characteristics of polypropylene (PP) and polyethylene (PE) were obtained from the polymerization over supported titanium–magnesium catalysts differing in their compositions (presence and absence of internal and external donors). Internal and external donors were found to affect the molecular weight of polymers in a different manner for ethylene and propylene polymerization. The introduction of the internal donor increases the molecular weight of PP and does not affect the mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…The glass‐transition temperature appeared at around −9 °C (see Figure S1). Similar phenomena have been reported in previous literatures . It can be found that the melting temperature ( T m ) and melting enthalpy (Δ H m ) gradually increased with proceeding of the polymerization for both catalysts.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The glass‐transition temperature appeared at around −9 °C (see Figure S1). Similar phenomena have been reported in previous literatures . It can be found that the melting temperature ( T m ) and melting enthalpy (Δ H m ) gradually increased with proceeding of the polymerization for both catalysts.…”
Section: Resultssupporting
confidence: 90%
“…Similar phenomena have been reported in previous literatures. [34][35][36] It can be found that the melting temperature (T m ) and melting enthalpy (ΔH m ) gradually increased with proceeding of the polymerization for both catalysts. However, the T m and ΔH m of PP catalyzed by Cat-1 were lower than those of PP catalyzed by Cat-2 under the same conditions.…”
Section: Activity and Polymer Chain Structurementioning
confidence: 99%
“…It should be noted that T m2 for PP3 produced over TMC‐0.1 is lower compared to PP6 produced over TMC‐3.5. The presence of two peaks on the DSC curves for PP samples produced at polymerization over TMC in the absence of an external donor was previously reported in ref …”
Section: Resultssupporting
confidence: 75%
“…2) lead to decreasing of the activity of the catalytic system and to decreasing of the polymer's molecular weight ( M w = 100 kg/mol). MWD is fairly narrow ( M w / M n = 5.0), which is ordinary for polyethylene that is produced on titanium–magnesium catalysts under similar conditions at 80 °C in the presence of hydrogen . Copolymerization in the presence of a comonomer (1‐hexene, exp.…”
Section: Resultsmentioning
confidence: 99%